Anthropometric profile of elite athletes of women´s futsal - Marcelo Romanzini; Sandra Aires Ferreira; Marcos Roberto Queiroga (Universidade Federal de Santa Catarina, 2005)
The objective of the present study was to determinate the somatotype profile of professional players of futsal by their tactical function. The sample was composed by 112 futsal players from ten teams from seven states that were disputing the 10th Brazilian Cup of Teams. The variables of body mass, stature, skinfold thickness, body perimeters and bone diameters were collected with the purpose of determining the somatotype and establishing the athletes' anthropometric profile. The data were analyzed by descriptive and Inferential statistics, which was accomplished by analyses of variance for repeated measures (ANOVA) followed by the Scheffé post-hoc test (p<0,05). The results demonstrated that the goalkeepers from women's futsal had a larger body mass when compared to other athletes, due, above all, to a larger accumulation of body fat, while the line athletes presented similar characteristics for the same variables. The mean athletes somatotype for all tactical functions was classified as mesomorphic. In summary, the results of the present study show that either the tactical function is not a decisive factor to cause morphologic modifications in these athletes, or these athletes' training is not appropriate for each position. Furthermore, the results of the present study can contribute to future comparisons as well as to thedesign of physical training.